Pengaruh Budaya dan Iklim K3 terhadap Kinerja Keselamatan dan Kesehatan Kerja pada Instalasi Pengeboran Lepas Pantai Rig Jack Up “X” - Edwin Joy Koreludji; Hari Eko Irianto; Sugiarto Sugiarto (Journal of Management and Creative Business, 2026)
The aim of this research is to find out the influence of safety Culture on safety performance at the “X” Jack-up Rig offshore drilling installation and to find out the influence of safety climate on safety Performance at the “X” Jack-up Rig offshore drilling installation.This type of research is quantitative. The population in this study was Jack Up Rig “X”. The sample in this study used Total Sampling, totally 59 workers in the Jack Up Rig “X”. The data collection technique used in this research was by using a questionnaire. Statistical analysis was carried out using the Partial Least Square-Structural Equation Modelling (PLS-SEM) approach.The results of this research show that: 1) The T-Statistics value (4.168) is greater than the T table value (2.001) and the P-value (0.000) which is smaller than 0.05, so the hypothesis H0 is rejected and H1 is accepted. This means that there is a significant positive (unidirectional) influence of safety culture on safety performance. 2) The T-Statistics value (3.258) is greater than the T table value (2.001) and the P-value (0.001) which is smaller than 0.05, then the hypothesis H0 is rejected and H1 is accepted. This means that there is a significant positive (unidirectional) influence of safety climate on safety performance.